2020
DOI: 10.3390/rs12193115
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Coarse-to-Fine Method of Ship Detection in Optical Remote Sensing Images Based on a Deep Residual Dense Network

Abstract: Automatic ship detection in optical remote sensing images is of great significance due to its broad applications in maritime security and fishery control. Most ship detection algorithms utilize a single-band image to design low-level and hand-crafted features, which are easily influenced by interference like clouds and strong waves and not robust for large-scale variation of ships. In this paper, we propose a novel coarse-to-fine ship detection method based on discrete wavelet transform (DWT) and a deep residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Optical remote sensing image, with its high spatial resolution, makes up for the shortage of other remote sensing data to a great extent and thus is widely used [10,11]. Still, the traditional ship classification algorithm of optical remote sensing images mostly uses manually designed features [9,[12][13][14], these features are easily affected by some clouds and waves, and the robustness is poor [15], which is not suitable for large-scale and multi-scene ship target recognition [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical remote sensing image, with its high spatial resolution, makes up for the shortage of other remote sensing data to a great extent and thus is widely used [10,11]. Still, the traditional ship classification algorithm of optical remote sensing images mostly uses manually designed features [9,[12][13][14], these features are easily affected by some clouds and waves, and the robustness is poor [15], which is not suitable for large-scale and multi-scene ship target recognition [16].…”
Section: Introductionmentioning
confidence: 99%
“…The latest research found that using a multi-scale feature extraction network to extract multi-scale features, the capacity to enhance model accuracies in ship extraction [28]. However, most networks only distinguish between ships and non-ships, with high intra-class variation causing misclassification [16]. Multiclass methods [12,16,29] provide a viable solution because the results have more categories, and more detailed ship information can be extracted.…”
Section: Introductionmentioning
confidence: 99%
“…However, the noisy response and low resolution of SAR images [11] may limit their utilizations. In recent years, attributing to the improvement of high-resolution technology, some researchers [12][13][14][15][16] have paid more attention to using optical remote sensing images because they could provide more details and spatial contents for detecting ships than SAR images.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the massive amount of generated ROIs, the computation is time-consuming and the model efficiency may be reduced. Chen et al [16] also designed a hierarchical detection process which applied discrete wavelet transform (DWT) to extract ship candidate regions and proposed deep residual dense network (DRDN) to improve the ship detection accuracy. The aforementioned two-stage detection methods mainly focus on improving the ship detection accuracy; however, they may ignore the detection speed.…”
Section: Introductionmentioning
confidence: 99%
“…Different excellent deep learning networks have been applied for feature extraction. For instance, in [13] a residual dense network is exploited to learn the features of different levels. Similarly, a pyramid structure is used to learn features of multi-scale rotating targets, which can accurately detect dense targets in various complex scenes [14].…”
Section: Introductionmentioning
confidence: 99%